Development of the Normative Regulation on the Official Latvian State Language During the First Period of Independence - Ringolds Balodis (Law: Journal of the University of Latvia, 2022)
The current article views the history of establishment and legal foundations of Latvian as the official language of the state, beginning from the position of Latvian among other languages in the newly established independent state of Latvia. The article includes not only analysis of works by other authors and publications in the area of research but also examination of transcripts of various joint sittings of legislators in different periods (the People’s Council, the Constitutional Assembly, the Saeima of the first and the second period of independence, and the Supreme Council), as well as unpublished minutes of committees. Within the article, certain part of the research focuses also on normative acts related to the use and protection of the official language. The author provides a detailed review of normative acts concerning the official language, concluding the study with the review of the period before the Soviet occupation – the situation after establishment of Kārlis Ulmanis’ authoritatian regime after the coup d’état on 15 May 1934.